Dissociation of behavioral and neural responses to provocation during reactive aggression in healthy adults with high versus low externalization - Kathrin Weidacker (Cognitive, Affective, and Behavioral Neuroscience, 2022)
The externalizing spectrum describes a range of heterogeneous personality traits and behavioral patterns, primarily characterized by antisocial behavior, disinhibition, and substance (mis)use. In psychopathology, abnormalities in neural threat, reward responses and the impulse-control system may be responsible for these externalizing symptoms. Within the non-clinical range, mechanisms remain still unclear. In this fMRI-study, 61 healthy participants (31 men) from the higher versus lower range of the non-clinical variation in externalization (31 participants with high externalization) as assessed by the subscales disinhibition and meanness of the Triarchic-Psychopathy-Measure (TriPM) performed a monetary modified Taylor-Aggression-Paradigm (mTAP). This paradigm consisted of a mock competitive-reaction-time-task played against a fictional opponent with preprogrammed win- and lose-trials. In lose-trials, participants were provoked by subtraction of an amount of money between 0 and 90 cents. As a manipulation check, provocation induced a significant rise in behavioral aggression levels linked with an increased activation in the anterior cingulate cortex (ACC). High externalization predicted reduced ACC responses to provocation. However, high externalizing participants did not behave more aggressively than the low externalization group. Additionally, the high externalizing group showed a significantly lower positive affect while no group differences emerged for negative affect. In conclusion, high externalization in the non-clinical range was related to neural alterations in regions involved in affective decision-making as well as to changes in affect but did not lead to higher behavioral aggression levels in response to the mTAP. This is in line with previous findings suggesting that aberrations at multiple levels are essential for developing externalizing disorders.